Effectiveness of Home science Vocational Training Programmes imparted by KVKs (Krishi Vigyan Kendras) - Ebrahim, Safia N; V., Girija (Journal of Extension Education, 2020)
Vocational training programmes play a positive role in the empowerment of women. The present study was planned with a specific objective to study the effectiveness of vocational trainings in home science discipline as rated by women trainees of a Krishi Vigyan Kendra (KVK). Training effectiveness was evaluated on five levels, viz. coverage, utility, teaching quality, knowledge and skill acquired. It was found that a great majority of trainees had perceived training as moderately effective. Programme effectiveness scores did not differ significantly among the four training groups. Mass media exposure, information seeking behavior, attitude towards training and entrepreneurial behavior had significant relationship with training effectiveness.